Catheter-Associated Candiduria: Aggregates, Microscopy, and CFU Variability - Stephan Steixner; Angelika Bauer; Rosa Bellmann-Weiler; Cornelia Lass-Flörl (Mycopathologia, 2026)
Diagnosis of catheter-associated candiduria is limited by absent colony-forming unit (CFU) thresholds and heterogeneous laboratory workflows, complicating patient management. Within a quality-improvement (QI) initiative we aimed to (1) implement and evaluate a standardised quantitative culture (QM) workflow for catheter urine, (2) compare QM with routine semi-quantitative culture (SQM) for CFU detection and reproducibility, and (3) assess whether visible urine aggregates predict Candida spp. presence. From February 2024 to February 2025, we analysed 222 yeast-positive urine samples from 74 catheterised patients. This pilot combined process standardisation, parallel SQM and QM testing, targeted microscopy of aggregate-containing samples, and species identification by CHROMID® Candida agar and MALDI-TOF. Agreement between methods, intra-patient CFU variability over three daily samples, and the predictive value of aggregates were assessed. Aggregates were present in 29/222 samples (13.1%), of which 13 (44.8%) contained Candida spp., mainly C. albicans. No reliable macroscopic features distinguished Candida -positive from -negative aggregates. QM and SQM showed poor agreement (Bowker p < 0.001, κ = 0.17). QM detected growth in samples reported as “sterile” by SQM and provided continuous CFU counts. Cohort-level median QM counts were stable, but 13 patients (17.6%) showed notable variability, with 5 (6.8%) fluctuating > 10 3 CFU/mL. Process data suggested batching and variable pre-analytics as contributors to discordance. A standardised QM workflow revealed substantial discordance with SQM and highlighted pre-analytical variability. Visible aggregates are unreliable indicators for Candida spp. presence. Adoption of standardised quantitative culture, systematic microscopy, and structured lab-clinician communication may improve diagnostic consistency; prospective evaluation is warranted.

Spaced out: An economic framework to explore the impacts of PV panel spacing on large-scale farming in Colorado - Brian Mirletz; James McCall; Samantha Bryan; Dala Al Mukhaini; Claire Nguyen; Sam Anderson; Stephan Weiler; Jordan Macknick (Agricultural Systems, 2026)

Optimal R&D investment in the management of invasive species - William Haden Chomphosy; Dale T. Manning; Stephanie Shwiff; Stephan Weiler (Ecological Economics, 2023)

Snap-fit assembly and upper limb functional limitations in automotive production workers: a nested case–control study - Johan Ohlander; Mekail-Cem Keskin; Stephan W. Weiler; Joachim Stork; Katja Radon (International Archives of Occupational and Environmental Health, 2019)

Abnormal labor outcomes as a function of maternal exposure to a catastrophic hurricane event during pregnancy - Sammy Zahran; Lori Peek; Jeffrey G. Snodgrass; Stephan Weiler; Lynn Hempel (Natural Hazards, 2013)

Correlates shift work with increased risk of gastrointestinal complaints or frequency of gastritis or peptic ulcer in H. pylori-infected shift workers? - Anke van Mark; Michael Spallek; David A. Groneberg; Richard Kessel; Stephan W. Weiler (International Archives of Occupational and Environmental Health, 2010)

Outpatient rehabilitation of workers with musculoskeletal disorders using structured workplace description - Stephan W. Weiler; Kay Peter Foeh; Anke van Mark; Rene Touissant; Nina Sonntag; Annette Gaessler; Johannes Schulze; Richard Kessel (International Archives of Occupational and Environmental Health, 2009)

Subcellular localization and tissue specific expression of amidase 1 from Arabidopsis thaliana - Stephan Pollmann; Daniel Neu; Thomas Lehmann; Oliver Berkowitz; Tina Schäfer; Elmar W. Weiler (Planta, 2006)

Occurrence and formation of indole-3-acetamide in Arabidopsis thaliana - Stephan Pollmann; Axel Müller; Markus Piotrowski; Elmar Weiler (Planta, 2002)